The Relationship between Ninth Graders' Perceptions of Teacher Equity and Their Math Identity: Differences by Student Race and School Racial Composition. Issue 2 (April 2023) - Shifrer, Dara; Phillippo, Kate; Tilbrook, Ned; Morton, Karisma
Using data on ninth graders, math teachers, and schools from the nationally representative High School Longitudinal Study of 2009, we investigate the following questions: (1) How do ninth graders' perceptions of their math teachers as equitable relate to their math identity at the intersection of adolescents' race and gender? and (2) Do differences in the percentage of students at the school who share the adolescent's race moderate (i.e., differentiate) the salience of perceptions of math teachers for adolescents' math identities? Our results suggest that adolescents who perceive their math teachers as equitable typically have higher levels of math identity regardless of their race or gender. Adolescents' perceptions of their math teachers as equitable are most salient for adolescents' math identity in racially diverse schools, where racial differences and stereotypes may be more visible. Findings also indicate the seeming resistance of Black youth to racist stereotypes, whose math identity remains high regardless of their perceptions of their teachers.